The implementation of recreational-educational concepts in the interior design of Rumah Seni Cemeti Yogyakarta: Implementasi konsep rekreatif edukatif pada perancangan interior Rumah Seni Cemeti Yogyakarta - Nufus, Zavira Hayatun; Ambarwati, Dwi Retno Sri (Universitas Negeri Yogyakarta, 2025)
This research aims to develop and implement the concept of educational recreation in the interior design of Cemeti Yogyakarta Art House. The method used in this research is the design thinking method, which has several stages, namely: (1) empathise; (2) define; (3) ideate; (4) prototype; (5) test. The design results include the design of zones, layouts, floors, walls, ceilings, and furniture. The design results have gone through a trial stage carried out using videos assisted by virtual reality tools and have met the assessment with four testers, namely building users, which resulted in an average score for the design feasibility indicator strongly agreeing 38.67%, agreeing 50%, disagreeing 10%, and disagreeing 16.33%, and indicators of the application of the concept of recreation and education resulted in an average score strongly agreeing 37.5%, agreeing 62.5%, disagreeing 0%. _______________________________________________________________________________ Penelitian ini bertujuan untuk menyusun dan mengimplementasikan konsep rekreatif edukatif pada perancangan interior Rumah Seni Cemeti Yogyakarta. Metode yang digunakan pada penelitian ini metode design thinking yang memiliki beberapa tahapan yaitu : (1) emphatize; (2) define; (3) ideate; (4) prototype; (5) test. Hasil perancangan meliputi perancangan zona, layout, lantai, dinding, plafon, dan furnitur. Hasil desain telah melalui tahapan uji coba yang dilakukan dengan menggunakan vidio yang dibantu dengan alat virtual reality dan telah memenuhi penilaian dengan 4 orang penguji yaitu pengguna bangunan, yang menghasilkan rata rata nilai untuk indikator kelayakan desain sangat setuju 38,67%, setuju 50%, kurang setuju 10%, dan tidak setuju 16,33%, dan indikator penerapan konsep rekreasi dan edukasi menghasilkan rata rata nilai sangat setuju 37,5%, setuju 62,5%, kurang setuju 0 tidak setuju 0%.